2017
DOI: 10.1103/physrevb.95.024515
|View full text |Cite
|
Sign up to set email alerts
|

Band geometry, Berry curvature, and superfluid weight

Abstract: We present a theory of the superfluid weight in multiband attractive Hubbard models within the BardeenCooper-Schrieffer (BCS) mean-field framework. We show how to separate the geometric contribution to the superfluid weight from the conventional one, and that the geometric contribution is associated with the interband matrix elements of the current operator. Our theory can be applied to systems with or without time-reversal symmetry. In both cases the geometric superfluid weight can be related to the quantum m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
274
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 194 publications
(293 citation statements)
references
References 69 publications
(132 reference statements)
19
274
0
Order By: Relevance
“…A flat band, which can be represented by δ function in the energy spectrum, is even more singular than a Van Hove singularity and leads to correlation induced novel phases which are qualitatively different from the phases appearing in presence of a Van Hove singularity [4]. Influence of the flat bands or quasiflat bands on different emergent novel phases of interacting lattice fermions, such as ferromagnetism [5][6][7][8], flat-band superfluidity [9][10][11], high-T c superconductivity of electron-doped compounds [12], non-Fermi-liquid behavior [13,14], and topological phases [15] have been explored theoretically. Experimentally, effects of flat bands have been reported in various real materials such as tetragonal La 4 Ba 2 Cu 2 O 10 [4], LaCo 5 and CePt 5 [16], and can be realized using ultracold atoms [17][18][19][20], where lattice geometry, and thus the singularities, can be well controlled.…”
Section: Introductionmentioning
confidence: 99%
“…A flat band, which can be represented by δ function in the energy spectrum, is even more singular than a Van Hove singularity and leads to correlation induced novel phases which are qualitatively different from the phases appearing in presence of a Van Hove singularity [4]. Influence of the flat bands or quasiflat bands on different emergent novel phases of interacting lattice fermions, such as ferromagnetism [5][6][7][8], flat-band superfluidity [9][10][11], high-T c superconductivity of electron-doped compounds [12], non-Fermi-liquid behavior [13,14], and topological phases [15] have been explored theoretically. Experimentally, effects of flat bands have been reported in various real materials such as tetragonal La 4 Ba 2 Cu 2 O 10 [4], LaCo 5 and CePt 5 [16], and can be realized using ultracold atoms [17][18][19][20], where lattice geometry, and thus the singularities, can be well controlled.…”
Section: Introductionmentioning
confidence: 99%
“…Now, the current operators (12), (13), the Green's function and the Hamiltonian all have the same structure as those for conventional BCS theory developed in [55]. Thus one can compute, by applying the Matsubara formalism and analytic continuation, the currentcurrent response function in a similar fashion as done in [55]. One starts from (11), inserts the expressions (12), (13) for the current operators, deploys the Matsubara formalism, applies the diagrammatic expansion up to first order diagrams and obtains , which vanishes at zero temperature if the quasiparticle spectrum is gapped.…”
Section: Derivation Of the Superfluid Weight In The Presence Of Soc Fmentioning
confidence: 99%
“…In [54,55] it was shown that in case of conventional BCS states the superfluid weight can be divided to two parts: the so-called conventional and geometric contributions, = + comprises the geometric properties of the Bloch functions. In a similar fashion than in [55], also in our case the superfluid weight can be split to conventional and geometric parts so that…”
Section: Derivation Of the Superfluid Weight In The Presence Of Soc Fmentioning
confidence: 99%
See 2 more Smart Citations